Penerapan Media Belajar Interaktif Berbasis Android Bagi Anak Desa Petuk Ketimpun Binaan Yayasan Ransel Buku - Bayu Pratama Nugroho; Norhayati Norhayati; Rosmiati Rosmiati; Susi Hendartie; Ferdiyani Haris; Sam'ani Sam'ani; Moch. Ichsan (Jurnal Pengabdian Masyarakat - PIMAS, 2022)
In order to improve the quality of learning, it is necessary to use information technology in learning media. The use of information technology and media in learning can form a learning atmosphere because students can actively participate. Nowadays, children are increasingly familiar and attached to smartphones or tablets. And when the world is entering the era of the industrial revolution 4.0. or the fourth world industrial revolution where technology has become the basis in human life, the use of information and communication technology for learning must start from the Early Childhood Education (PAUD) level so that it can be more interesting and interactive and increase children's interest and curiosity in what is taught. . The method of applying science and technology is using mobile technology which is very popular today, namely an Android-based children's learning application as an effort to increase knowledge and understanding as well as increase interest in learning for the children of the Petuk Ketimpun village which is under the guidance of the Palangkaraya Book Backpack Foundation. The purpose of implementing this program is to increase knowledge and understanding and increase children's interest in learning about various things including letters, numbers, colors, vegetables, animals, fruit, work and vehicles. Both in Indonesian and English pronunciation through the implementation of learning applications for Android-based children.